The study of Islamic law in Ahmad Ibrahim Kulliyyah of Law (AIKOL), International Islamic University Malaysia (IIUM) - Othman, Ahmad Azam (2007)
The principle aim of establishing the International Islamic University Malaysia (IIUM) is to offer courses that integrate both secular (non religious) and Islamic (religious) curriculum. Therefore, the study of Islamic Law (Shariah) constitutes an important component in the legal education at Ahmad Ibrahim Kulliyyah of Laws (AIKOL) as it is an integral part to the system. The curriculum is designed in such a way that the civil law subjects are taught in parallel to the Islamic Law subjects. The idea is to give exposure to the students of both disciplines, able to make comparison and to learn from both systems in order to come out with best practices. The graduates from AIKOL are able to practice in both civil as well as the Shariah courts as Malaysian law recognizes dual jurisdiction. At Postgraduate level, AIKOL introduces two professional courses to assist practitioners and administrators i.e., Postgraduate Diploma in Shariah Legal Practice (DSLP) and Diploma in Administration and Islamic Judiciary (DAIJ). The former is designed for those who graduate from other law schools with no Shariah background while the latter is for those who have Shariah background where the emphasis is made on the study of the applicable law as applied in Malaysia. AIKOL introduces also Master of Comparative Law where the nature of study is comparative in nature. For the purpose of enrollment, the candidate with no Shariah background has to take Shariah course as a prerequisite while the candidate with no civil law background has to take civil law subjects. The idea is to assist the student in the learning process that provides for comparative approach. The same concept is imposed for doctoral thesis and Master by research where the candidate is encouraged to write at least one chapter on Shariah or vice versa.